High Uric Acid Decrease the Number of Erections in Night: A Propensity Score-Matched Analysis - Wang, Shangren; Zhang, Aiqiao; Niu, Shuai; Pan, Yang; Liu, Xiaoqiang (Urology Journal, 2025)
Background: Metabolic syndrome is considered a risk predictor for erection dysfunction (ED). However, the effect of serum uric acid (UA) on the development of ED is little known. Methods: We adopt propensity score matching analysis (PSM) to adjust multitudinous confounding factors such as age, metabolic syndrome, sex hormone and some blood measurements. The members of the normal UA and high UA participator were matched at a 1:1 ratio by propensity score. And we used two diagnostic methods IIEF-5 and nocturnal penile tumescence and rigidity (NPTR) to assess and diagnose ED. Results: Before PSM, total 120 participators were included, compared with participants with normal serum UA (n=61), those with high serum UA(n=59) had statistic difference in some baseline information (BMI 27.8 ± 7.4 vs 24.4 ± 5.1 kg/m2, p = 0.004; TG 2.1 ± 1.8 vs 1.5 ± 0.9 mmol/L, p = 0.015; creatinine 70.5 ± 9.9 vs 66.3 ± 10.7 umol/L, p = 0.03; T 450.9 ± 181.0 vs 598.2 ± 186.3 ng/dL, p < 0.001). After PSM, total 82 participators were included, with high level of serum UA (n = 41, Group A) and normal serum UA (n = 41, Group B). On the result of IIEF-5, 40 of 41 participants (97.6.0%) with high UA diagnosed ED, whereas 39 of 41 participants (95.1%) with normal UA diagnosed ED, the incidence has no statistical significance between two groups (p > 0.999). On the result of NPTR, the mean number of erections in Group A was 4.1 ± 2.0, was significantly less than the same parameter in Group B (5.3 ± 1.9, p = 0.004); 9 of 41 participants (22.0%) with high UA develop ED, whereas 14 of 41 participants (34.1%) with normal UA develop ED, the incidence has no statistical significance between Group A and Group B (p = 0.326). Conclusions: Our study revealed that high UA did decrease the number of erections in night, which was diagnosed by NPTR. High uric acid may be a potential risk factor for ED and more large studies are needed.